INTEGRASI METODE COMMUNITY LANGUAGE LEARNING DAN STRATEGI THINK TALK WRITE TERHADAP MAHARAH KALAM - Aufa Nadiya Farhani; Muhammad Akmansyah; Koderi (Universitas Islam Negeri Mataram, 2026)
This study aims to analyze the effectiveness of integrating the Community Language Learning method and the Think Talk Write strategy in developing maharah kalam (Arabic speaking skills) through a systematic literature review of scholarly publications from 2020 to 2025. The main problem identified is students’ low fluency and lack of confidence in speaking Arabic, which stem from speech anxiety and insufficient cognitive structuring in the language production process. The research employs the Systematic Literature Review method, encompassing stages of exploration, selection, and thematic synthesis of fifteen peer-reviewed articles indexed in SINTA, DOAJ, and Google Scholar that are relevant to the implementation of Community Language Learning and Think Talk Write. The findings reveal that Community Language Learning effectively reduces the affective filter, enhances motivation, and fosters a humanistic and supportive learning environment. Meanwhile, Think Talk Write strengthens idea planning, speech cohesion, and linguistic production skills through the sequential phases of thinking, discussing, and writing. The synthesis of results indicates that the integration of these two approaches produces a significant affective-cognitive synergy: Community Language Learning mitigates emotional barriers, while Think Talk Write optimizes cognitive readiness and utterance structuring. This combination consistently enhances students’ fluency, coherence, and oral participation, although grammatical accuracy improvement still requires additional corrective feedback. It is concluded that the integrative model of Community Language Learning and Think Talk Write is a viable and innovative pedagogical framework for reinforcing the teaching of maharah kalam in a communicative, collaborative, and sustainable manner